Pharmacokinetics of Bupropion and Its Pharmacologically Active Metabolites in Pregnancy - Fokina, Valentina M. (Drug Metab Dispos, 2016)
Bupropion sustained release is used to promote smoking cessation in males and nonpregnant females. However, its efficacy as a smoking cessation aid during pregnancy is not reported. The pregnancy-associated changes in maternal physiology may alter the pharmacokinetics and pharmacodynamics of bupropion and consequently its efficacy in pregnant smokers. Therefore, the aims of this study were to determine the steady-state pharmacokinetics of bupropion during pregnancy and the effect of functional genetic variants of CYP2B6 and CYP2C19 on bupropion pharmacokinetics in pregnant women. Plasma and urine concentrations of bupropion and its metabolites hydroxybupropion (OHBUP), threohydrobupropion, and erythrohydrobupropion were determined by liquid chromatography–mass spectrometry. Subjects were genotyped for five nonsynonymous single-nucleotide polymorphisms that result in seven CYP2B6 alleles, namely *2, *3, *4, *5, *6, *7, and *9, and for CYP2C19 variants *2, *3, and *17. The present study reports that the isoform-specific effect of pregnancy on bupropion-metabolizing enzymes along with the increase of renal elimination of the drug could collectively result in a slight decrease in exposure to bupropion in pregnancy. In contrast, pregnancy-induced increase in CYP2B6-catalyzed bupropion hydroxylation did not impact the plasma levels of OHBUP, probably due to a higher rate of OHBUP glucuronidation, and renal elimination associated with pregnancy. Therefore, exposure to OHBUP, a pharmacologically active metabolite of the bupropion, appears to be similar to that of the nonpregnant state. The predicted metabolic phenotypes of CYP2B6*6 and variant alleles of CYP2C19 in pregnancy are similar to those in the nonpregnant state.